Effect of progress variable definition on the mass burning rate of premixed laminar flames predicted by the Flamelet Generated Manifold method. Issue 4 (7th June 2021) - Gupta, Harshit; Teerling, Omkejan J.; van Oijen, Jeroen A.
Abstract : This paper investigates how the choice of progress variable in tabulated chemistry affects the mass burning rates of premixed laminar flames. Simulations are carried out using finite rate, detailed chemistry (DC) and Flamelet Generated Manifolds (FGM) . Through comparison of detailed chemistry and FGM (using different progress variable definitions), it is found that for FGM the mass burning rate depends on the choice of progress variable and thus results in a different mass burning rate than detailed chemistry. Since the mass burning rate is influenced by stretch and transport phenomena, the effects of these on mass burning rates are analysed. While FGM qualitatively predicts the effect of stretch on the mass burning rate compared to detailed chemistry, there are quantitative differences. It is shown that this is mainly caused by a lack of projection in usual FGM applications. When the projection of the source term and the diffusion term are included in the table, FGM becomes independent of the choice of progress variable and the effects of stretch are better represented by FGM similar to detailed chemistry.